PERILAKU KOMUNIKASI NONVERBAL ANAK AUTIS DALAM PROSES BELAJAR DI SMPN 46 SURABAYA - Lestari, Dewi Ayu; Sjafi’i, Achmad; Satvikadewi, A.A.I. Prihandari (representamen, 2016)
Communication is done not only verbally but nonverbal communication often we use to deliver the message. Nonverbal communication is also used by autistic children to interact with their environment. The formulation of research problem is how nonverbal communication behavior of autistic children during the learning process in SMPN 46 Surabaya along with the meaning of nonverbal communication shown by children with autism are nonverbal communication during the learning process in SMPN 46 Surabaya and to categorize the meaning of nonverbal communication hehavior of an autistic child demonstrated during the learning process takes place that uses kinesics communication theory as a reference. The result of this study indicate that nonverbal communication shown by children with autism is very diverse. However, by using kinesic Theory of Communication as a reference it can be seen how nonverbal communication shown children with autism as well as the meaning of nonverbal communication that is shown by the autistics child. Keyword: Nonverbal Communication, Autism, Kinesic Theory, Behavior Communcation